Optimal. Leaf size=27 \[ x-\log \left (\frac {-\frac {1}{x}+e^{4 x} x}{2 (1+x)}\right ) \]
________________________________________________________________________________________
Rubi [F] time = 1.23, antiderivative size = 0, normalized size of antiderivative = 0.00, number of steps used = 0, number of rules used = 0, integrand size = 0, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.000, Rules used = {} \begin {gather*} \int \frac {-1-3 x-x^2+e^{4 x} x \left (-x-3 x^2-3 x^3\right )}{-x-x^2+e^{4 x} x \left (x^2+x^3\right )} \, dx \end {gather*}
Verification is not applicable to the result.
[In]
[Out]
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \frac {1+3 x+x^2-e^{4 x} x \left (-x-3 x^2-3 x^3\right )}{x (1+x) \left (1-e^{4 x} x^2\right )} \, dx\\ &=\int \left (-\frac {1+2 x}{x \left (-1+e^{2 x} x\right )}+\frac {1+2 x}{x \left (1+e^{2 x} x\right )}+\frac {-1-3 x-3 x^2}{x (1+x)}\right ) \, dx\\ &=-\int \frac {1+2 x}{x \left (-1+e^{2 x} x\right )} \, dx+\int \frac {1+2 x}{x \left (1+e^{2 x} x\right )} \, dx+\int \frac {-1-3 x-3 x^2}{x (1+x)} \, dx\\ &=\int \left (-3-\frac {1}{x}+\frac {1}{1+x}\right ) \, dx-\int \left (\frac {2}{-1+e^{2 x} x}+\frac {1}{x \left (-1+e^{2 x} x\right )}\right ) \, dx+\int \left (\frac {2}{1+e^{2 x} x}+\frac {1}{x \left (1+e^{2 x} x\right )}\right ) \, dx\\ &=-3 x-\log (x)+\log (1+x)-2 \int \frac {1}{-1+e^{2 x} x} \, dx+2 \int \frac {1}{1+e^{2 x} x} \, dx-\int \frac {1}{x \left (-1+e^{2 x} x\right )} \, dx+\int \frac {1}{x \left (1+e^{2 x} x\right )} \, dx\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.20, size = 23, normalized size = 0.85 \begin {gather*} x+\log (x)+\log (1+x)-\log \left (1-e^{4 x} x^2\right ) \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.77, size = 24, normalized size = 0.89 \begin {gather*} x + \log \left (x + 1\right ) - \log \left (\frac {x e^{\left (4 \, x + \log \relax (x)\right )} - 1}{x}\right ) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.87, size = 21, normalized size = 0.78 \begin {gather*} x - \log \left (x^{2} e^{\left (4 \, x\right )} - 1\right ) + \log \left (x + 1\right ) + \log \relax (x) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.10, size = 22, normalized size = 0.81
method | result | size |
risch | \(x +\ln \left (x +1\right )-\ln \left (x \,{\mathrm e}^{4 x}-\frac {1}{x}\right )\) | \(22\) |
norman | \(x +\ln \relax (x )-\ln \left (x \,{\mathrm e}^{4 x +\ln \relax (x )}-1\right )+\ln \left (x +1\right )\) | \(23\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.41, size = 40, normalized size = 1.48 \begin {gather*} x + \log \left (x + 1\right ) - \log \relax (x) - \log \left (\frac {x e^{\left (2 \, x\right )} + 1}{x}\right ) - \log \left (\frac {x e^{\left (2 \, x\right )} - 1}{x}\right ) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 5.37, size = 23, normalized size = 0.85 \begin {gather*} x+\ln \left (x+1\right )-\ln \left (\frac {x^2\,{\mathrm {e}}^{4\,x}-1}{x}\right ) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.21, size = 20, normalized size = 0.74 \begin {gather*} x - \log {\relax (x )} + \log {\left (x + 1 \right )} - \log {\left (e^{4 x} - \frac {1}{x^{2}} \right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________